Demographics Differences in the Microfinance Clients' Perception Towards Islamic Microfinance: The Case Of Nigeria - Abdullateef Abdulqadir Maikabara; Abdulmajeed M.R Aderemi; Sri Maulida (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2020)
This paper investigates the different perceptions of microfinance clients' demographic characteristics towards Islamic microfinance. The convenience sampling technique was adopted to select the study sample to collect data from the microfinance clients' beneficiaries in Kwara state. Four hundred data were obtained and analyzed on SPSS Version 25 using descriptive analysis, independent sample t-test, and one-way ANOVA. The findings indicate a statistically significant difference in the microfinance beneficiaries' perception of their demographic region, age, marital status, religion, and education level.